#IfTheyGunnedMeDown: An Analysis of Mainstream and Social Media in the Ferguson, Missouri, Shooting of Michael Brown. (March 2018) - Everbach, Tracy; Clark, Meredith; Nisbett, Gwendelyn S.
Focusing on the hashtag #IfTheyGunnedMeDown, this study examined the framing of mainstream newspaper coverage of social media activism in the aftermath of the 2014 police shooting of Michael Brown in Ferguson, Missouri. People of color primarily used the hashtag to draw attention to what they perceived as negative stereotypes perpetuated by the news media. The study employed a textual analysis of news coverage combined with semistructured interviews with hashtag-protest participants. The analysis found that the mainstream media followed news production rituals by relying primarily on elite, established sources and generally ignoring the social media protestors' voices. The social media protestors who used the hashtag said they used it to bypass the mainstream media, and this research indicates they may well have done so and possibly reached a younger generation that relies more on social media than legacy media.